Intersectionality and Participatory Action Research - Giada Bonu (Culture e Studi del Sociale)
The article intends to explore, through the account of an empirical research on feminist spaces in urban contexts between Rome and Madrid, a proposal for the intertwining of Participatory Action Research and Intersectionality. To begin laying the foundations on which the research was developed, the article briefly traces the genealogy of participatory research and, on the other hand, the encounter with intersectionality. Afterwards, the article explores this intersection through three empirical perspectives: positionality; the intertwining of PAR and intersectionality in research planning with participants; and the intertwining in data analysis and dissemination of results. All three aspects seem to point to certain recurring elements: PAR, informed by an intersectional approach, allows the expression of the voice of a range of subjects, going beyond the possibility of expression that certain social power structures preclude; the participatory approach breaks the monopoly of the academy's production of knowledge, which is often male, white, Western, heterosexual, cis, ableist, opening up counter-narratives acted out by the subjects themselves embodying subaltern positions.